2003
DOI: 10.1086/376532
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Serum and Urinary Antibody for Diagnosis of Tuberculosis

Abstract: Efforts to devise immunoassays for tuberculosis (TB) that can be adapted to rapid formats are ongoing. The present study was aimed at determining whether urinary anti-Mycobacterium tuberculosis antibodies are present in patients with TB, to evaluate the feasibility of developing a urine antibody-based diagnostic test. Urinary antibodies directed against the culture filtrate proteins of M. tuberculosis, MPT 32, and the 81-kDa GlcB protein were detectable in patients with TB, although the sensitivity of antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…Malate synthase (81 kDa), present in M. tuberculosis culture filtrates, the cell wall, and cytoplasmic subcellular fractions, is an enzyme of the glyoxylate pathway used by M. tuberculosis during intracellular replication in macrophages (90) and has adapted to function as an adhesin that enhances bacterial adherence to host cells (46). In sputum smear-positive patients, malate synthase achieved a sensitivity of 73% (95% CI, 58 to 85) and a specificity of 98% (95% CI, 95 to 100) (35,37,85,86,108). The likelihood ratio positive (40.78) was considerably higher for malate synthase than for other antigens.…”
Section: Resultsmentioning
confidence: 99%
“…Malate synthase (81 kDa), present in M. tuberculosis culture filtrates, the cell wall, and cytoplasmic subcellular fractions, is an enzyme of the glyoxylate pathway used by M. tuberculosis during intracellular replication in macrophages (90) and has adapted to function as an adhesin that enhances bacterial adherence to host cells (46). In sputum smear-positive patients, malate synthase achieved a sensitivity of 73% (95% CI, 58 to 85) and a specificity of 98% (95% CI, 95 to 100) (35,37,85,86,108). The likelihood ratio positive (40.78) was considerably higher for malate synthase than for other antigens.…”
Section: Resultsmentioning
confidence: 99%
“…Our systematic studies of humoral responses in TB patients have identified a panel of potential candidates for devising a rapid POC test for TB, and immunodominant epitopes of some of these highly immunogenic M. tuberculosis antigens have been delineated (11,34,36,39,43,44). Since combinations of multiple antigens provide an increased sensitivity of antibody detection (11,15,17,42,53), it is likely that combinations of immunodominant epitopes from multiple highly immunogenic proteins of M. tuberculosis will enable the development of a peptide-based rapid test for TB. One or more of the six epitopes of LipC defined in these studies could make significant contributions to such a diagnostic test.…”
Section: Discussionmentioning
confidence: 99%
“…Reactivity of guinea pig or human sera with LFCFP or lysates of E. coli expressing His-tagged PPE-C protein or purified His-PPE-C protein was tested by Western blotting as described previously (44). Briefly, LFCFP, lysates of E. coli expressing the PPE-C protein, appropriate control lysates, or purified PPE-C protein was fractionated on 10% SDS-polyacrylamide gels under reducing conditions, and the Western blots were probed with anti-His monoclonal antibody (MAb) or E. coli lysate-absorbed sera from guinea pigs or humans (1:100) (23).…”
Section: Methodsmentioning
confidence: 99%